Amrubicin in patients with platinum-refractory metastatic neuroendocrine carcinoma and mixed adenoneuroendocrine carcinoma of the gastrointestinal tract. Issue 8 (September 2016) - Araki, Tomonori; Takashima, Atsuo; Hamaguchi, Tetsuya; Honma, Yoshitaka; Iwasa, Satoru; Okita, Natsuko; Kato, Ken; Yamada, Yasuhide; Hashimoto, Hironobu; Taniguchi, Hirokazu; Kushima, Ryoji; Nakao, Kazuhiko; et al.
Abstract : Although the same treatment strategy as used for small cell lung cancer, including second-line chemotherapy, is generally applied to metastatic neuroendocrine carcinoma (NEC) and mixed adenoneuroendocrine carcinoma (MANEC) of the gastrointestinal tract (GIT; GIT-NEC/MANEC), the efficacy of amrubicin (AMR) for GIT-NEC/MANEC is not well known. We retrospectively analyzed platinum-refractory GIT-NEC/MANEC patients who received AMR between February 2004 and July 2012 at the National Cancer Center Hospital. The AMR dose administered was 30–45 mg/m 2 on days 1–3 every 3–4 weeks. The overall response rate according to Response Evaluation Criteria in Solid Tumors guidelines, version 1.0, progression-free survival, overall survival, and adverse events by National Cancer Institute-Common Terminology Criteria for Adverse Events guidelines, version 4.0 were evaluated. Nineteen patients received AMR. The response rate for 16 assessable patients was 18.8% (95% confidence interval, 4.1–45.7), the median progression-free survival was 3.8 months (2.3–5.3), and the median overall survival was 7.7 months (7.1–8.2). Grade 3/4 neutropenia occurred in 52.6% of patients and febrile neutropenia occurred in 10.5%. Other nonhematological toxicities were mild and treatment-related deaths were not observed. AMR may have a modest effect, with tolerable toxicities, on patients with platinum-refractory GIT-NEC/MANEC. Further prospective evaluations are warranted.